High-grade neuroendocrine carcinoma of the lung: Comparative clinicopathological study of large cell neuroendocrine carcinoma and small cell lung carcinoma - Sun, Lihua; Sakurai, Shinji; Sano, Takaaki; Hironaka, Mitsugu; Kawashima, Osamu; Nakajima, Takashi (Pathology international, 2009)
Large cell neuroendocrine carcinoma (LCNEC) and small cell lung carcinoma (SCLC) are high‐grade neuroendocrine carcinomas. In order to clarify the similarities and differences between these cancers, 22 cases each of LCNEC and SCLC were collected and a comparative pathological study was carried out. First, their clinicopathological characteristics were confirmed, which were very similar to those previously reported. The 5 year survival rate of LCNEC and SCLC patients was 38.3% and 29.7%, respectively. The morphological characteristics of LCNEC and SCLC were then reviewed with regard to the morphology previously used to differentiate these cancers. As a result, many morphological indicators, such as tumor cell size, nuclear/cytoplasmic ratio, nuclear molding, rosette formation, prominent nucleoli and karyolysis were confirmed to be significant indicators for distinguishing LCNEC from SCLC. On comparative immunohistochemistry, LCNEC had significantly high staining scores for the expression of keratin 7 and 18, E‐ and P‐cadherins, β‐catenin, villin 1, retinoblastoma protein (pRB), c‐met and α‐enolase. These results might reflect the differentiation or deviation of LCNEC toward an epithelial nature irrespective of neuroendocrine tumor lineage. In conclusion, the present comparative study of LCNEC and SCLC defined the similarities and differences between these cancers, and showed the biologically and clinicopathologically overlapping spectrum of the tumor lineage.